Nurses' ideas about the age-related evolution of the subject's qualities: Dynamics and resources - Sizova, Larisa А.; Tolochek, Vladimir A. (Saratov State University, 2023)
The relevance of the study is determined the following: increase in the duration of a person’s working life and the expansion of the articulate components of its quality create a socially and psychologically signifi cant “second reality”, by which we mean subjective ideas about one’s profession, about one’s career, and about their social success. The research purpose is to study the ideas of the professional activity subjects about the age-related evolution of their qualities. The article hypothesizes the following ideas: 1) The subjects’ ideas about their professional and working life act as conditions that aff ect the dynamics of their professional evolution. 2) Social experience acts as a factor that infl uences the subjects’ ideas about the age-related evolution of their qualities. Participants: nurses (N = 82), women aged from 21 to 67, Regional Clinical Hospital No. 1 named after Professor S. V. Ochapovsky (Krasnodar). Methods (tools): the locus of subjective control was determined by means of the subjective control questionnaire (SCQ) (J. Rotter adapted by E. F. Bazhina, S. A. Golykina, A. M. Etkind); the original author’s methodology (“Dynamics of Professional Career Questionnaire”) (L. A. Sizova, V. A. Tolochek), which includes several groups of the most informative questions (previously tested and characterized by satisfactory reliability as the technique ‘items’): A) ideas about the dynamics of positive development, that is the development of professionally important qualities at the age of 20–65: 1) learning ability; 2) intuition in the professional sphere; 3) physical performance; 4) intellectual performance. B) ideas about the dynamics of the negative phenomena increase at the age of 20–65: 1) occupational destructions; 2) occupational diseases; 3) life crises. The third set of questions (C) is focused on the respondents’ refl ection on the role of various “factors” in their professional development. Such factors as parents, relatives, friends, family members, work groups, special circumstances, science, art, and religion are considered. The fourth block (D) took into account the socio-demographic and offi cial job-position characteristics of the respondents. Results: working hypotheses have been confi rmed. The research shows that: 1) the use of the original author’s methodology made it possible to identify important “nodes” in the studied connections and determinants, and to identify both typical and professionally specifi c features of the dynamics of the subjects’ age-related evolution; 2) when getting the task of presenting their integral working life, people adequately describe its overall dynamics. At the same time, the level of refl ection in the sample as a whole seems to be insuffi cient, adequate not in every aspect; 3) the subjects’ assessments (nurses of a large medical institution) of the role of external conditions, which optimize and/or aggravate the dynamics of evolution/involution of their qualities and functions, are liable to the powerful infl uence of indirect factors (media, etc.). This refl ects the relevant tasks of correcting negative distortions of social perception of fragments of social reality, as well as the real possibilities of managing people’s ideas about their professional career. Main conclusions: the issue of professional careers in the areas with a “fl at hierarchy” is of current importance and requires further study.